Training on Preparing BUMDes Financial Reports - Widiastuti, Retno; Magdalena, Marlina; Bakhrudin; Purnomo, Hari; Fatimah, Annisa; Jarnuzi, Ahmad (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Purpose -This Community Service Activity (PKM) was carried out in order to provide training in preparing financial reports based on SAK ETAP and KEPMEN Desa No. 136 of 2022 with the help of the Village BUM Financial Recording and Reporting Application (PPAK). This training in preparing financial reports is a means of increasing transparency and accountability in the use of village funds for BUMDes Pulotondo, Ngunut District, Tulungagung Regency, which has been established since 2015 and has never prepared financial reports.   Design/methodology/approach – The method used in this PKM activity is: 1. Presentation of Material. Presentation of material regarding the steps for preparing financial reports is carried out by the lecturer together with students majoring in Accounting by explaining the material that has been prepared. 2. Practice. The practice of preparing financial reports using the BUM Desa Financial Recording and Reporting (PPAK) application is carried out by Lecturers and Accounting Department Students by showing/demonstrating directly how to use the application directly to the village officials managing BUMDes Pulotondo so that they are able to understand the work steps and know what should be done next.   Findings- The results that have been achieved with this training activity in preparing BUMDes financial reports are that village officials managing BUMDes have been greatly helped by this training because they have understood the steps in preparing financial reports and what reports must be presented so that they are in accordance with SAK ETAP and KEPMEN Desa No. 136 which requires BUMDes managers to prepare financial reports using the PPAK application. By preparing this financial report, it is hoped that BUMDes Pulotondo, Ngunut District, Tulungagung Regency can increase financial transparency and accountability as required by the government through the Ministry of Villages, Disadvantaged Regions and Transmigration. In accordance with Village Ministerial Decree No. 136   Originality/value – The implication of this community service is that BUMDes Pulotondo already has knowledge of how to prepare financial reports in accordance with SAK ETAP and Village Ministerial Decree No. 136. The novelty of this community service is the use of the Village BUM Financial Recording and Reporting (PPAK) application which was launched by the Ministry of Villages, Disadvantaged Regions and Transmigration at the end of 2022.